Manajemen Risiko Operasional Pada Bank Syari'ah Indonesia di Jawa Timur - Anggitaningsih , Retna (Multidisciplinary Journal of Education , Economic and Culture, 2024)
This research is motivated by the operational risk that occurs at Bank Syariah Indonesia (BSI). Therefore, effective operational risk management is needed at BSI. The purpose of this study is to examine in depth the implementation of operational risk management at BSI. This study uses a qualitative research approach. The data in this study uses secondary data or literature studies. Secondary data obtained from the official BSI website, books, journals and articles related to the research. The data analysis technique used is the qualitative data analysis technique of the Miles and Huberman model. The results of this study are that operational risk management at BSI has been implemented effectively. This is evidenced by the BSI BOPO ratio during 2021 to 2022 which continues to decline